Exophthalmos due to odontogenic intraorbital abscess in Cebus apella - Oriá, Arianne P.; Pinna, Melissa H.; Estrela-Lima, Alessandra; Gomes Junior, Deusdete Conceição [UNESP]; Libório, Fernanda A.; Assis Dórea Neto, Francisco de; Oliveira, Alberto V. D.; Nogueira, Marcos; Requião, Katia (Wiley, 2013)
Background: The accumulation of pus in the orbit originating from an infected dental root is classified as odontogenic intraorbital abscess. Methods: Clinical, laboratory, and image evaluation of a non-human primate was performed. Results: The patient was cured after surgical therapy. Conclusions: This represents the first report of an odontogenic periodontal abscess in Cebus apella. © 2013 John Wiley & Sons A/S. Published by Blackwell Publishing Ltd.
Keywords: Enucleation; Exenteration; Primate; azithromycin; enrofloxacin; flotril; garamacina; gentamicin; ketoprofen; unclassified drug; animal cell; animal tissue; antibiotic therapy; Cebus; cebus apella; clinical feature; computer assisted tomography; cytodiagnosis; drug substitution; drug withdrawal; exophthalmos; male; medical history; nonhuman; odontogenic intraorbital abscess; orbit infection; periorbital edema; prescription; priority journal; weight reduction; Animals; Exophthalmos; Male; Monkey Diseases; Orbit; Periodontal Abscess; Cebus apella; Primates